The effect of using podcast audio-assisted listening to improve listening comprehension - Ikrima, Adella Raihani Siti; Fahriany, Fahriany; Nahartini, Desi (Universitas Sarjanawiyata Tamansiswa, 2023)
This research was conducted in the third semester of English Education students at university. Understanding listening is crucial for communicating in a foreign language since it is the most fundamental of the four primary developing language skills. Nevertheless, this skill seems to be the most difficult to master. This research aimed to obtain evidence supporting the effect of applying podcast audio-assisted listening. A quasi-experimental design specially used in experimental and control classes consists of 60 students through online meetings. The pre-test and post-test were used with a listening test. The experimental class mean score increased from 72.07 to 85.53, and the 2-tailed P significance was less significant (0.006 < 0.05) than the alpha. As a result, Ha is accepted, and Ho is rejected. The results showed an effect size of 0.75 had a moderate effect, and the percentage of N-gain was 56.45%, meaning it has been effective enough to use podcast audio-assisted listening. Additionally, students' listening comprehension can be improved by using podcast audio-assisted listening. During the treatment, students also improved with new vocabulary and knew various accents. However, researchers are encouraged to apply the podcast media in person rather than through an online meeting. Moreover, the sample can choose a podcast they are interested in from a selection of podcast audio related to the researchers' study. It is recommended to use podcasts so that students can engage with the listening content.